Novel low-delta value troponin algorithms have good precision for rule-out of NSTE-ACS. (25th November 2020) - Tjora, H; Steiro, O.T; Langorgen, J; Omland, T; Collinson, P; Bjorneklett, R.O; Nygard, O.K; Skadberg, Ø; Bonarjee, V.V.S; Vikenes, K; Aakre, K.M
Abstract: Background: Rapid rule-out algorithms for non-ST-elevation infarction (NSTEMI) may be beneficial for logistics in the emergency room. Current algorithms are designed to rule-out NSTEMI, but do not differentiate between unstable angina (UAP) in need of revascularization and non-cardiac chest pain patients (NCCP) who could be discharged. Recent improvements in analytical precision of high sensitivity troponin (cTn) assays allow for trialing algorithms with very small delta values. Purpose: Could the use of lower delta values produce rule-out algorithms for NSTE-ACS with a false negative rate of ≤5%, and a sufficient high rule-out rate of patients with NCCP. Method: 927 patients with suspected NSTE-ACS were consecutively included. Serum samples were collected at 0, 3 and 8–12 hours. The final diagnosis was adjudicated by two independent cardiologists based on all clinical data including routine cTnT. The 0- and 3-hour samples were additionally measured for cTnIand cTnI from Singulex Clarity System (cTnI(sgx)). The diagnostic performance to rule-out NSTE-ACS was compared between one low-delta value algorithm from each assay (cTnT, cTnI and cTnT). Results: The prevalence of NSTEMI was 13.4%, UAP 11.4% and NCCP 60%. Median age was 63 years, 60% males. Fig. 1 shows baseline and 3-hour delta cTn values for the UAP and NCCP patients for the three different assays. The baseline cTn value differed significantly between UAP and NCCP for all assays, p value <0.001. The novel low-delta cTnT algorithm (Table 1) ruled out 8 NSTE-ACS patients (3.5%), the cTnI algorithm and cTnI (sgx) algorithm ruled out 11 (4.8%) and 12 (5.2%) patients with NSTE-ACS, respectively. Moreover, the cTnT algorithm allocated 35.3% of the NCCP patients to discharge. Respective numbers for the cTnI(sgx) and cTnI algorithm were 30.6% and 33.5%. Comparing the ROC curves, the cTnT algorithm had significantly higher AUC compared to the cTnI(sgx) algorithm (p value =0.005, DeLong test). Conclusion: The low-delta value algorithms correctly ruled in ≥95% of the NSTE-ACS patients whilst >30% of NCCP patients were ruled out. The cTnT algorithm had the best performance with a significant higher AUC compared to the cTnI(sgx) algorithm. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Western Norway Regional Health Authority, Haukeland and Stavanger University hospital